Main methods to detect Multiple Sclerosis (MS) lesions in patients with MS - Almutairi, Abdullah Dhaifallah; Mahmud, Rozi; Suppiah, Subapriya; Abu Hassan, Hasyma (Universidad del Zulia, 2019)
The aim of the study is to investigate the main methodsto detect Multiple Sclerosis (MS) Lesions in patientswith MS. This study was a systematic review to detect main methods to detect of MS lesion in patients with MS. As a result, we found that MRI is the most accuracy and powerful tool for diagnosing a MS especially in early phase. In conclusion, the McDonald criteria is the best criteria that it has been proposed and revised in recently years to diagnose of MS based on clinical presentation and MRI.